2018
DOI: 10.29252/pcnm.8.1.28
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Role of Serum Leptin Levels in Pregnant Mothers in Relation to their Delivery Type

Abstract: Background: It seems that in vaginal delivery, serum leptin level increases as a cortisol-dependent factor due to the stress of the embryo. Studies have shown that if the level of serum leptin is low, the risk of chronic metabolic diseases, cardiovascular diseases, hypertension, and obesity in the mother and the baby will increase. Objectives: The aim of this study was to determine the relationship between serum leptin levels in pregnancy and the type of delivery. Methods: This study was a descriptive-analytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Our study showed no association between maternal serum leptin levels and maternal age, gestational age of the fetus, fetal weight and gender and mode of delivery. In agreement, different studies revealed no significant differences in maternal serum leptin concentrations in regard to fetal birth weight [ 4 , 6 , 15 ] and mode of delivery [ 6 , 33 , 36 ]. On the other hand, other studies reported a positive correlation between maternal serum leptin levels and fetal birth weight [ 11 , 37 ] and gestational age of the fetus [ 36 ].…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Our study showed no association between maternal serum leptin levels and maternal age, gestational age of the fetus, fetal weight and gender and mode of delivery. In agreement, different studies revealed no significant differences in maternal serum leptin concentrations in regard to fetal birth weight [ 4 , 6 , 15 ] and mode of delivery [ 6 , 33 , 36 ]. On the other hand, other studies reported a positive correlation between maternal serum leptin levels and fetal birth weight [ 11 , 37 ] and gestational age of the fetus [ 36 ].…”
Section: Discussionsupporting
confidence: 72%
“…The demographic and clinical characteristics of the study population are summarized in Table 1 . The median age of women was 31 [ [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] ] years and the median body mass index was 29.9 [27.3–33.2] kg/m 2 . The reported medical illnesses and antenatal complications were 48 (10.6%) and 139 (30.8%) respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations